2017
DOI: 10.1038/s41598-017-11776-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into streptozotocin-induced diabetic rats from the protein misfolding perspective

Abstract: Protein folding is a process of self-assembly defined by the sequence of the amino acids of the protein involved. Additionally, proteins tend to unfold, misfold and aggregate due to both intrinsic and extrinsic causes. Human islet amyloid polypeptide (hIAPP) aggregation is an early step in diabetes mellitus. However, the aggregation of rat IAPP (rIAPP) remains an open question. Adult female Sprague-Dawley rats weighing 150–250 g were divided into two groups. The experimental group (streptozotocin [STZ]) (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Toxic oligomers in pancreatic islets can be found in non-transgenic mice [41]. Similarly, Leyva-García and colleagues found responsive material to antibody anti oligomer-like immunoreactive material (“anti-amyloid oligomer”, A11 antibody) on streptozotocin-induced mice [42]. These findings corroborate with previous identification of aggregated amylin on diabetic and elder nondiabetic individuals [43].…”
Section: Introductionsupporting
confidence: 66%
“…Toxic oligomers in pancreatic islets can be found in non-transgenic mice [41]. Similarly, Leyva-García and colleagues found responsive material to antibody anti oligomer-like immunoreactive material (“anti-amyloid oligomer”, A11 antibody) on streptozotocin-induced mice [42]. These findings corroborate with previous identification of aggregated amylin on diabetic and elder nondiabetic individuals [43].…”
Section: Introductionsupporting
confidence: 66%
“…Sometimes these results can cause confusion in the results’ reading ( Figure 3 and Figure 4 , Table 2 ). In our group we have demonstrated that the rat IAPP hexamers are diagnostic biomarkers of the onset and progression of diabetes mellitus and play a role as therapeutic targets [ 20 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, we now know that the soluble amyloid oligomers—the most cytotoxic and the cause of death of target cells (in the brain, pancreas, etc. )—of conformational diseases are characterized by [ 11 , 15 ]: Low Molecular weight (trimers (10–15 kDa), hexamers (24–30 kDa) [ 20 ]. Contain β-sheet-rich structures [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, proteins tend to unfold, misfold and aggregate due to intrinsic and extrinsic causes [ 1 , 2 , 3 ]. Unfolding and aggregation of proteins gives way to what is known as “conformational diseases (CDs)”: One of the most challenging CDs is diabetes [ 1 , 4 , 5 , 6 , 7 , 8 ]. The prevalence of diabetes is increasing rapidly: 29.1 million people or 9.3% of the population of the USA has diabetes resulting in a total cost of $245 billion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%